Comparative analysis of neonatal weight and length pattern in cross-cradle and other breastfeeding positions - Solanki, Vishnu H.; Shah, Maitri C.; Parmar, Sanjay P.; Memakiya, Krishna K. (International Journal of Contemporary Pediatrics, 2024)
Background: Breastfeeding is an art and a skill which needs to be learnt and mastered. There is no one right position for breastfeeding. Any breastfeeding position that is comfortable for the mother and infant for effective breast milk transfer is an acceptable position. Cross cradle hold works well for Mothers who are breastfeeding for the first time, with latching difficulties, having flat and inverted nipples. Also, it helps in deep latching which helps to improve the level of attachment among new born. Objective of the study was to compare cross-cradle hold and other breastfeeding positions in terms of their effects on weight and length pattern in neonates among primiparous breastfeeding mothers after full-term vaginal delivery. Methods: This prospective cohort study was conducted in the obstetrics and gynaecology department among 240 primipara mothers who delivered vaginally at the same tertiary care institute. Results: Total 50.42% mothers preferred cross-cradle hold breastfeeding position. Neonates of mothers who had adopted cross-cradle hold, had better gain in weight and length after one month. Conclusions: Significantly more gain in weight and length of neonates were observed in those mothers who have adopted cross-cradle breastfeeding position.